2017
DOI: 10.5152/tao.2017.2769
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Verruca Vulgaris Presenting with Dysphonia: A Case Report

Abstract: Verruca vulgaris is a common skin lesion that is associated with human papilloma virus and is observed on the surface of skin. Verruca vulgaris is rarely seen in mucosal membranes. Atypical locations may be confused with verrucous carcinoma. The incidence of laryngeal verruca vulgaris has not yet been reported in the literature. Differential diagnoses in histopathological examinations include keratosis, squamous papilloma, verrucous hyperplasia, and verrucous carcinoma. Distinguishing disease from verrucous ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Hyperkeratotic papilloma is differentiated from the most common type verruca vulgaris on histopathological examination where the later shows presence of atypia and koilocytosis in the spinous layer. 10 This case also emphasizes on the differential diagnosis of laryngeal papillomatous lesion and the effect of chronic exposure to smoke in an immunosuppressed individuals…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Hyperkeratotic papilloma is differentiated from the most common type verruca vulgaris on histopathological examination where the later shows presence of atypia and koilocytosis in the spinous layer. 10 This case also emphasizes on the differential diagnosis of laryngeal papillomatous lesion and the effect of chronic exposure to smoke in an immunosuppressed individuals…”
Section: Discussionmentioning
confidence: 88%
“…Histopathological examination showed hyperkeratosis, hypergranulosis, koilocytes in the spinous layer confirming the diagnosis of Verruca vulgaris. 10 Keisuke et al reported a case of vocal cord actinomycosis where a 49 year old male patient presented with voice change since 2 years and has an irregular lesion over vocal cord which mimicked a laryngeal papilloma or tumor. Histopathological examination showed actinomycosis with vocal nodule which was treated with appropriate antibiotics.…”
Section: Discussionmentioning
confidence: 99%